COVID-19 beyond DAD: Persisting microcirculation thrombosis, hidden infections, and early pulmonary fibrosis as remaining challenges of the disease - Lilian V.S. Carvalho; Cassiana da Silva Souza; Jonathan L.M. Fontes; Lara Cardoso; Milton Salomar; Amaro Nunes Duarte-Neto; Claudio Figueira; Reginaldo Brito; Bianca Mesquita; Luiz A.R. de Freitas; Geraldo G.S. Oliveira; Washington L.C. dos-Santos (Elsevier, 2022)
Background: Despite advances in the management of COVID-19, some events occurring in the course of disease still represent challenges to patient treatment. Case presentation: Here we present a case of severe COVID-19 in which the patient received standard treatment including dexamethasone and prophylactic anticoagulation and died on the 24th day of disease. Autopsy showed exudative and proliferative DAD accompanied by remaining microcirculation thrombosis despite anticoagulation treatment, unperceived fungal infection, concomitantly with the presence of dense acellular fibrotic areas amidst organizing lung lesions. Conclusions: Although improvements were achieved in COVID-19 therapeutics lung microcirculation coagulopathy, unperceived fungus infection and early developing alveolar fibrosis remain unsolved problems associated to the disease.